2008
DOI: 10.1021/ef800332m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Stroke/Bore Ratio on the Performance Parameters of a Dual-Spark-Ignition (DSI) Engine

Abstract: In this study, the effects of the stroke/bore (S/B) ratio on the performance parameters of an engine having dual-spark ignition (DSI) were investigated theoretically by using a quasi-dimensional thermodynamic cycle model. A range of S/B ratios for various spark-plug locations were examined in the scope of the study. The engine performance parameters, i.e., engine power, indicated mean effective pressure, specific fuel consumption, and thermal efficiency, were computed for various conditions. The obtained resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…As a result, a small B/S ratio design usually shows higher combustion efficiency and thermal efficiency. 8,9,11,[16][17][18][19][20] However, as the engine speed increases, the advantage of long stroke would be gradually lost as the friction loss significantly increases. 8 It is also reported that the reduced convection heat losses at part load could compensate the unfavorable surface/volume ratio for a ''square'' design with B/S ratio of 1, resulting in fuel consumption benefits by improving the reciprocating and rotating components stress and friction at high speed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, a small B/S ratio design usually shows higher combustion efficiency and thermal efficiency. 8,9,11,[16][17][18][19][20] However, as the engine speed increases, the advantage of long stroke would be gradually lost as the friction loss significantly increases. 8 It is also reported that the reduced convection heat losses at part load could compensate the unfavorable surface/volume ratio for a ''square'' design with B/S ratio of 1, resulting in fuel consumption benefits by improving the reciprocating and rotating components stress and friction at high speed.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition to the fuel conversion efficiency, the variation in the B/S ratio also shows impacts on exhaust emissions. As the B/S ratio increases, the increased crevice volume could lead to increased carbon monoxide (CO) and hydrocarbon (HC) emissions, 17,18 but lower nitrogen oxide (NOx) emissions. 17 Compared to the four-stroke engines, the performance of two-stroke engines is more affected by the B/S ratio because of its direct impact on the scavenging process of the two-stroke cycle operation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu çalışmanın odağında BA motorlarda çift buji ile ateşleme yönteminin kullanımı bulunmaktadır. Çift buji ile ateşleme yönteminde; silindir kafasında eksenel simetrik [13,14] veya diyagonal [15] olarak yerleştirilmiş iki adet buji yer almaktadır. Bujilerde ateşleme işlemi çalışma koşullarına bağlı olarak eş zamanlı veya sıralı olarak yapılabilmektedir [16].…”
Section: Gi̇ri̇ş (Introduction)unclassified